D-Dimer Predicts Disease Severity but Not Long-Term Prognosis in Acute Pulmonary Embolism. (12th July 2019) - Geissenberger, Fabian; Schwarz, Florian; Probst, Michael; Haberl, Sabine; Gruetzner, Stefanie; Kroencke, Thomas; von Scheidt, Wolfgang; Berghaus, Thomas M.
D-dimer might be correlated with prognosis in pulmonary embolism (PE). The predictive value of plasma D-dimer for disease severity and survival was investigated in the lowest and highest D-dimer quartile among 200 patients with PE. Patients with high D-dimers were significantly more often hypotensive ( P = .001), tachycardic ( P = .016), or hypoxemic ( P = .001). Pulmonary arterial obstruction index (PAOI) values were significantly higher in the high D-dimer quartile ( P < .001). Elevated troponin I (TNI) levels ( P < .001), simplified PE severity indices ≥1 ( P < .001), right-to-left ventricular (RV/LV) diameter ratios ≥1 ( P < .001), and thrombolysis ( P = .001) were more frequent in the high D-dimer quartile. D-dimer was associated with RV/LV ratios ≥1 ( P = .021), elevated PAOI ( P < .001) or TNI levels ( P < .001), hypotension ( P < .001), tachycardia ( P = .003), and hypoxemia ( P < .001), but not with long-term all-cause mortality. D-dimer predicts disease severity but not long-term prognosis in acute PE, possibly due to a more aggressive treatment strategy in severely affected patients.